Breaking the silence through MANTRA: Empowering Tamil MAN survivors of torture and rape - Fernandes, Pearl; Aiello, Yvette (Torture Journal, 2018)
Introduction: The prevalence of sexual torture, including rape as a form of torture against men in the context of war and persecution, has been widespread throughout history and across cultures. Despite this, literature examining this highly complex and pervasive problem has only recently begun to emerge. This is partly a reflection of the taboo nature of the topic, which results in lack of disclosure, a poor understanding of the issue, and leads to gaps in effective therapeutic interventions. Objective: This paper aims to provide a reflective narrative on an intervention trialled at the NSW Service for the Treatment and Rehabilitation of Torture and Trauma Survivors (STARTTS). It outlines the therapeutic strategies that were integrated in culturally sensitive ways and the phases and themes that emerged as the men overcame their resistance to speak about their experiences of torture. Results: The combination of group and individual therapy that integrates exposure therapy in a culturally appropriate way can assist clients to revisit their traumatic experiences and ‘break their silence’ as they heal and recover. Conclusions: When male survivors of sexual torture share and verbalise their past horrors it assists them to make meaning and develop a new, broader perspective, on their experiences. Accompanied by a diminishing sense of shame, and “therapeutic activism” it instils hope and the motivation to assist others in crisis, particularly regarding the issue of male rape.